EVERYTHING IS READY; COME TO THE MARRIAGE BANQUET: The Parable of the Invitation to the Royal Marriage Banquet (Matt 22:1-14) in the Context of Matthew’s Gospel - Joseph, Nalpathilchira (Asian Horizons, 2012)
This study is an exegetical investigation into the meaning and function of Jesus’ Parable of the Invitation to the Royal Marriage Banquet (Matt 22:1-14) in the context of the First Gospel. Formulated as a thesis, the present study argues that the parable in Matt 22:1-14 is mainly not paraenetical or polemical but revelatory, and that by the parable, which is the most influential and powerful means used by Jesus to speak about the reign of heaven, he is making clearer the dynamism operative in the kingdom of heaven.